PENGARUH KECEPATAN PEMAKANAN DAN KECEPATAN PUTARAN SPINDEL TERHADAP TINGKAT KEKASARAN PERMUKAAN MATERIAL ASSAB 709 / SCM 440 PADA PROSES BUBUT - Ratnawati, Ratnawati; Santoso, Tri; Yuono, Lukito Dwi (TURBO [Tulisan Riset Berbasis Online], 2024)
Surface roughness resulting from the machining process is an important part in determining the quality of the workpiece. In an effort to increase effectiveness and quality in making products using the lathe process, research to determine the surface roughness value of the lathe process is very necessary. In this research, the lathe process was carried out by setting variations in spindle speed and variations in feed motion and a fixed cutting depth of 0.5 mm. The spindle speeds used are 370 rpm, 540 rpm & 800 rpm. Meanwhile, the feed speed used is 0.05 mm/rev, 0.10 mm/rev & 0.20 mm/rev, so the feed speed used in this research is 18.5 mm/minute, 27 mm/minute, 40 mm /minute, 80 mm/minute & 160 mm/minute. This research uses ASSAB 709/SCM 440 material because this material is a medium alloy steel which is often used to make spare parts for both industrial and automotive machines but its application requires different roughness values - different. In this study, the surface roughness value resulting from the turning process from variations in feed speed & machine spindle speed was measured using a Mitutoyo SJ 210 roughness measuring instrument.The results of the lathe process with variations in feed speed & machine spindle speed using ASSAB 709/ SCM 440 material which were measured using the Mitutoyo SJ 210 surface roughness tester, the best average roughness value obtained was 0.354 Ra or the equivalent of N5 using the spindle rotation speed parameter 800 rpm and feed speed 40 mm/minute